E-commerce as a Consequence of Innovation and the Cause of New Innovations for SMEs: the Perspectives of Latvia and Lithuania - Baiba Rivza; Maiga Kruzmetra; Peteris Rivza; Astrida Miceikiene; Alvydas Balezentis; Jonas Jasaitis (Comparative Economic Research. Central and Eastern Europe, 2020)
The emergence of new technologies and the expansion of digitalisation have created an opportunity for e-commerce to develop. A supplier and a buyer of goods and services meet in the e-environment and solve their problem without direct contact, which is mutually beneficial. Accordingly, when it comes to globalisation, e-commerce, as a system, becomes an important topic of research in general, and, in particular, it is vital for small and medium enterprises (SMEs), since most enterprises in the European Union (EU) are SMEs. Latvia and Lithuania are EU Member States, and SMEs are dominant in these two Baltic States. The aim of the research is to identify and compare the opinions of producers/sellers and buyers on the positive contribution of e-commerce to date and the problems caused by e-commerce for both sides. The research employed data from Eurostat, OECD and the Central Statistical Bureau of Latvia as well as the authors' own data from a survey (e-commerce users: suppliers (n=112) and buyers (n=138) of goods and services) conducted in Latvia and Lithuania. An analysis of the statistical data reveals the current objective position of e-commerce in both countries. The proportion of small and medium enterprises involved in this process is increasing. At the same time, the processing of the results of the e-commerce survey enables the authors to see a subjective view of this process, which includes both positive and negative features of both the buyers and the sellers. Identifying problems and comparing the situations in the two neighbouring countries opens the way to find e-commerce development directions and reduce the problems not only economically but also geographically and ethnically, as the objective data on e-commerce are not identical for Latvia and Lithuania, even though the data are positive and only slightly different.
Keywords: M37; O14; 330; e-commerce; SMEs; innovation; motivation